2015
DOI: 10.1111/jora.12191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Parent, Sibling, and Peer Support During the Transition to Young Adulthood

Abstract: Longitudinal trajectories of parent, sibling, and peer support during the transition to young adulthood were compared among 600 participants (51.1% female) from Asian, European, and Latin American backgrounds. Participants completed questionnaires at 12th grade, 2 and 4 years after high school. Results indicated that parent support increased across this period for participants from European backgrounds but remained stable for participants from Asian and Latin American backgrounds. Peer and sibling support rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 97 publications
7
100
2
6
Order By: Relevance
“…Accumulating research has demonstrated the integral role of the family in Latino youth development, with previous research demonstrating close links between family cultural values, close supportive relationships, and daily family activities with Latino youth adjustment and well-being (Berkel et al, 2010; Gonzales et al, 2012; Guan & Fuligni, 2016; Zeiders, Updegraff, Umaña-Taylor, McHale, & Padilla, 2015). Yet, few studies have adopted a cultural neurobiological approach to understanding how qualities of the family, ranging from everyday family assistance behaviors to cultural values, are associated with physiological stress processes and subsequent health.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research has demonstrated the integral role of the family in Latino youth development, with previous research demonstrating close links between family cultural values, close supportive relationships, and daily family activities with Latino youth adjustment and well-being (Berkel et al, 2010; Gonzales et al, 2012; Guan & Fuligni, 2016; Zeiders, Updegraff, Umaña-Taylor, McHale, & Padilla, 2015). Yet, few studies have adopted a cultural neurobiological approach to understanding how qualities of the family, ranging from everyday family assistance behaviors to cultural values, are associated with physiological stress processes and subsequent health.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, parental and adolescent reports of relationship quality tend to diverge quite substantially, with mothers overestimating both the overall positivity of relationships and the severity of occurring conflicts (Collins & Laursen 2004;Steinberg 2001). Between late adolescence and early adulthood, parental and adolescent views of their relationship increasingly converge, and reported conflict becomes less frequent, whereas perceptions of support and closeness gradually recover (Collins & Laursen 2004;Guan & Fuligni 2016).…”
Section: The Present Studymentioning
confidence: 99%
“…In adolescence, some families undergo a phase of increased parent-adolescent conflict and authority struggle, which is reflected in decreased parental warmth and support (Collins & Laursen 2004;Guan & Fuligni 2016). In the extreme, such conflicts predict poor psychosocial adjustment in adolescents (Collins & Laursen 2004).…”
Section: The Role Of Life Stagementioning
confidence: 99%
“…Late adolescence is an especially interesting period of development as individuals encounter many environmental changes such as moving away from home, transitioning from education to employment, and starting a family, which can provide additional environmental stressors. Social support is a key factor in helping young adults navigate these major life changes 5,6 , but these environmental changes can bring about instability and changes to an individual’s social circle itself, and an individual’s perceptions of support from others can change dramatically during this time 79 .…”
Section: Introductionmentioning
confidence: 99%
“…However, no such distinction has been investigated specifically in late adolescence. This distinction is especially important to look at during this time given the individual’s changes in both social network structure (support quantity) 8 and support perception (quality) 9 during this time.…”
Section: Introductionmentioning
confidence: 99%